2017
DOI: 10.1186/s12906-017-1658-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold sensitivity in the extremities on circulating adiponectin levels and metabolic syndrome in women

Abstract: BackgroundIn adipose tissues, adipokine levels, including adiponectin and leptin, are involved in insulin sensitivity and are reciprocally induced by cold temperature stress. Thermogenic response in the extremities (hands and feet) against cold stress can be negatively related to fat mass accumulation, particularly in the abdomen. However, the relationship between the sensation of cold in the extremities and circulating levels of adipokines is not fully understood. Here, we investigated whether adipokine level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
5
20
0
Order By: Relevance
“…Classically, endothelial dysfunction has been regarded as an integrative measure of cardiovascular risk comprising other traditional factors such as hypertension and metabolic syndrome, the integral of all risk factors. FS challenges our view in the presence of endothelial dysfunction in a collective that is diametrically opposed to the typical patient at risk for cardiovascular events: active, slim, normo-or hypotensive, and less prone to metabolic syndrome [126]. Is too much of good bad?…”
Section: Conclusion: Two Endotheliopathies Two Collectives At Riskmentioning
confidence: 93%
“…Classically, endothelial dysfunction has been regarded as an integrative measure of cardiovascular risk comprising other traditional factors such as hypertension and metabolic syndrome, the integral of all risk factors. FS challenges our view in the presence of endothelial dysfunction in a collective that is diametrically opposed to the typical patient at risk for cardiovascular events: active, slim, normo-or hypotensive, and less prone to metabolic syndrome [126]. Is too much of good bad?…”
Section: Conclusion: Two Endotheliopathies Two Collectives At Riskmentioning
confidence: 93%
“…This can be explained by the low frequency of classical cardiovascular risk factors such as arterial hypertension, hypercholesterolemia, obesity, or diabetes. However, people with increased cold sensitivity in the extremities are additionally protected against metabolic syndrome, probably by an increased level of adiponectin [ 7 ]. Nevertheless, FS can be a risk factor for some diseases discussed in this review.…”
Section: Flammer Syndrome As a Protective Factormentioning
confidence: 99%
“…The development of an objective pattern identification process has long been desired in order to standardize the diagnostic process of TEAM. Recent studies have shown that various objective variables have significant associations with cold pattern including anthropometric measures such as body mass index [ 39 ], resting metabolic rate [ 4 ], heart rate variability parameters [ 8 ], adiponectin [ 40 ], norepinephrine, and changes in glucose and insulin during oral glucose tolerance testing [ 5 ]. Together with these previous findings, we hope that our results contribute to the formation of an objective pattern identification system and understanding the underlying mechanism of cold pattern.…”
Section: Discussionmentioning
confidence: 99%